African Cities and International Migration Governance: From Glocal Identities to Multilevel Solutions? - Stürner-Siovitz, Janina (Journal of International Affairs, 2022)
At the Africities Summit 2018, African city representatives discussed the role of local authorities in the UN Global Compacts for Migration and Refugees and adopted the Charter of Local and Subnational Governments of Africa on Migration. At first glance, this municipal engagement may seem surprising, given that most African cities lack mandates for action on migration at the local, let alone the international level. However, in practice, a growing number of migrants and refugees are settling in African cities, whose local authorities are therefore confronted with core issues of international migration governance. Lacking adequate funding, resources and national support, some African cities strive to engage in city diplomacy defending their interests and seeking collaboration at higher levels of governance. To better understand and theorize this empirical development, this article asks, how do African cities claim agency and develop action in regional and global migration governance? Contributing to a multidisciplinary dialogue between migration studies, urban studies and international relations literature, the article seeks to expand research on city diplomacy into an under-researched policy field and to overcome a geographic research bias on cities from the Global North. The analytical framework builds on Acuto’s seminal analysis of an international city identity. Combining a qualitative structuring content analysis of official city declarations and statements with an analysis of 25 expert interviews, the article finds that representatives from African cities present cities as actors holding glocal positions, agency, and responsibilities on questions of urban migration. Building on this actor framing, African city representatives argue that municipal cooperation is essential for ensuring that regional and global migration policy-making reflects local realities and is implemented in outcome-oriented and context-specific ways. City representatives draw on this actor framing to move from calls for agency to proactive and predominantly hybrid forms of action—co-shaping narratives on human mobility, setting transnational municipal standards, and demanding a voice in intergovernmental deliberations.
Keywords: Africa; cities; migration; city diplomacy

African city diplomacy in global climate mobility debates - Stürner-Siovitz, Janina; Morthorst, Lasse Juhl (Global Networks - A Journal of Transnational Affairs, 2024)
While researchers have paid growing attention to transnational city engagement in both the policy fields of migration and climate change, there is a dearth of studies exploring how cities claim agency and start acting in emerging global climate mobility debates. Moreover, city diplomacy research tends to focus predominantly on city actors from the global North. We aim to address this research bias and advance academic debates by exploring African city diplomacy in global climate mobility debates. Specifically, we examine the question: How do African cities claim recognition as relevant actors in global dialogues on climate mobility, and what kind of action do they take? To find answers, we draw on a role theory framework analysing empirical research undertaken within an international, interdisciplinary research project.
CRIS-Team Scopus Importer:2024-03-22
Keywords: Africa; city diplomacy; climate mobility; role theory; transnationalism

African City Diplomacy – Municipal Purpose and Action in Transnational Migration Governance - Stürner-Siovitz, Janina (Trialog, 2022)
Keywords: Africa; cities; refugees; migration

"All the World's a Stage?" A Role Theory Analysis of City Diplomacy in Global Migration Governance - Stürner-Siovitz, Janina (International Migration Review, 2022)
In 2018, cities from Africa, Europe, North, and South America officially submitted input to the state-led negotiations of the Global Compact for Migration. In the same year, the Mayors Mechanism was established within the Global Forum on Migration and Development, and in 2019, cities made pledges to localize the Global Compact on Refugees. At first sight, this engagement seems surprising, given that migration and displacement are mostly areas of national decision making. How, then, did it become possible for cities to claim a role in global migration governance? And how do cities attempt to play this role? While cities as integration actors have received growing academic attention, it is time to focus on city agency in global migration governance. To explore this phenomenon, this article introduces role theory to research on city diplomacy in migration studies. The analysis shows that the combination of the glocalized representation of migration challenges (linking the local and global levels), the glocal role claimed by cities, and the passive role attributed to nation-states can empower cities to demand an active role in global migration governance. Cities draw on this role to promote three forms of city diplomacy as adequate and feasible actions on the global stage: advocating for rights-based migration policies; striving to gain access to international funding and cooperation partners; and demanding a seat at intergovernmental negotiation tables. In closing, the article reflects on the risks and constraints of city diplomacy in global migration governance and shows directions for future research.
CRIS-Team WoS Importer:2023-01-27

A Local Turn for European Refugee Politics - Recommendations for Strengthening Municipalities and Local Communities in refugee and asylum policy of the EU - Bendel, Petra; Heimann, Christiane; Schammann, Hannes; Stürner, Janina (2019)
The European Union’s migration and asylum policy is in deep crisis. Initiatives by individual nation states are the order of the day. A common «area of freedom, security and justice» is still only a distant prospect. In search of new ideas to stop this trend it has increasingly been suggested that the competences of cities and municipalities when it comes to the reception of refugees should be strengthened.At the same time, the EU Com-mission is promoting the involvement of the municipal level in various policy areas with a range of activities such as the «Urban Agenda for the EU». Ultimately it is the municipalities themselves which, despite a lack of legal competences, are speaking out more clearly on questions of migration policy. In recent years they have coped with the accommodation and care of refugees, despite facing a number of challenges. Now they want to have a say when it comes to the opening or closing of borders and the reception of persons seeking protection. City networks such as Solidarity Cities bear witness to this self-confidence, as do the offers by the mayors of Naples, Barcelona, Bonn and numerous other municipalities to take in the passengers of rescue ships. This initiative failed, however, largely due to the national governments. The municipalities still appear to be in too weak a position institutionally to effectively help shape EU asylum policy. There are still no coherent strategies which are both innovative and feasible. This is the starting point for this paper. It demonstrates the financial and structural deficits of the municipalities in respect of asylum and refugee policy and develops specific ideas as to how municipalities can be strengthened sustainably, and their potential be used for the further development of a common European asylum system. Municipalities should, for example, be given improved access to EU funds and a say in the reception of persons seeking protection. At the same time, the right to self-determination of and suggestions put forward by persons in need of protection should be taken seriously: secondary movements can only be reduced significantly if refugees are able to participate in the choice of place of residence. The proposals connect promising approaches from the professional discourse in politics and academia and take them further. Gesine Schwan was a particularly prominent advocate of the call for municipalities to be strengthened as independent actors with an EU fund in EU refugee policy. This and similar demands have recently been taken up by France’s president, Emmanuel Macron as well as by Green Party MPs, for example Franziska Brantner. The recommendations have been debated with experts from both researchers and politicians from different political fields. They can be adapted to the structures and processes in the respective member state and implemented in accordance with national policy. The scope of the proposals is based mainly on political feasibility and practicability. The proposals can be divided into three groups: the organisation of European funds, the strengthening of multi-level governance and the development of a municipal relocation mechanism. <br
Keywords: European Refugee Politics; Local Communities; Asylum Policy

A New Role for Cities in Global and Regional Migration Governance? - Stürner, Janina (2020)
Keywords: migration; governance; cities; policy-making

Bildungsangebote für Geflüchtete: Kommunale Koordinierung und Vernetzung am Beispiel Stuttgart - Stürner, Janina (2017)
Keywords: Stadt; Integration; Politik

Challenging the Nation-State from within: The Emergence of Transmunicipal Solidarity in the Course of the EU Refugee Controversy - Heimann, Christiane; Mueller, Sandra; Schammann, Hannes; Stürner, Janina (Social Inclusion, 2019)
In the context of the so-called refugee crisis, political disputes about solidarity become a central issue with member states applying competing concepts. At the same time, European cities use transnational networks to implement a new form of solidarity among municipalities via city diplomacy (Acuto, Morissette, & Tsouros, 2017). Analyzing the deadlock between member states and the emerging activities of cities, we scrutinize the limits of existing approaches to political solidarity (e.g., Agustin & Jorgensen, 2019; Knodt, Tews, & Piefer, 2014; Sangiovanni, 2013) to explain this phenomenon. Based on expert interviews and document analysis from a study on transnational municipal networks, we identify an emerging concept of solidarity that challenges the nation states as core providers of solidarity from within: transmunicipal solidarity focuses on joint action of local governments to scale out and scale up.
CRIS-Team WoS Importer:2019-07-16

Cities as Migration Governance Partners - Stürner-Siovitz, Janina; Heimann, Christine (2023)
Keywords: governance; migration; cities; global; local

Curtain up City diplomancy in global migration governance - Stürner, Janina (Springer VS, 2022)
Curtain up explores city diplomacy in global migration governance. The author lays out the paradox that cities, although increasingly de facto migration actors in an urbanizing world, lack channels to influence international policies that directly impact local realities. Drawing on ten case studies from around the world, the author shows that local governments strive to overcome this paradox through global-level interaction with national and international actors contributing to the emergence of a role of cities in global migration governance. Cities draw on this role to influence migration narratives, place local issues on global agendas and demand a seat at decision-making tables. Advancing the analysis of cities as global-level actors, the author introduces role theory to migration studies and presents a series of timely policy recommendations. These set out concrete steps towards a stronger institutionalization of city diplomacy in global migration governance. This book is written for scholars of migration studies, urban studies, and international relations as well as for practitioners focusing on multi-level migration governance, city diplomacy and multi-stakeholder partnership
Keywords: city diplomacy; migration; governance

Der Weg über die Kommunen - Empfehlungen für eine neue Schlüsselrolle der Kommunen in der Flüchtlings- und Asylpolitik der EU - Bendel, Petra; Heimann, Christiane; Schammann, Hannes; Stürner, Janina (2019)
Die Migrations- und Asylpolitik der Europäischen Union ist in einer tiefen Krise. Alleingänge von Nationalstaaten sind an der Tagesordnung. Ein gemeinsamer «Raum der Freiheit, der Sicherheit und des Rechts» scheint in weite Ferne gerückt. Auf der Suche nach Ideen, um diesen Trend aufzuhalten, wird in jüngster Zeit vermehrt vorgeschlagen, Städte und Gemeinden in ihren Kompetenzen bei der Aufnahme von Geflüchteten zu stärken. Gleichzeitig treibt die EU-Kommission mit diversen Aktivitäten, wie der «Urban Agenda for the EU» den Einbezug der kommunalen Ebene in diversen Politikfeldern voran. Nicht zuletzt sind es die Kommunen selbst, die sich trotz mangelnder rechtlicher Kompetenzen immer deutlicher in migrationspolitischen Fragen zu Wort melden. Sie haben in den letzten Jahren die Unterbringung und Versorgung Geflüchteter trotz mancher Herausforderung bewältigt. Nun wollen sie auch mitsprechen, wenn es um die Öffnung oder Schließung von Grenzen und die Aufnahme von Schutzsuchenden geht. Städtenetzwerke wie Solidarity Cities zeugen von diesem Selbstbewusstsein ebenso wie die Angebote der Bürgermeister/innen von Neapel, Barcelona, Bonn und zahlreicher anderer Kommunen, die Passagiere von Rettungsschiffen aufzunehmen. Dieser Vorstoß scheiterte jedoch größtenteils an den jeweiligen nationalen Regierungen. Noch scheinen die Kommunen institutionell zu schwach aufgestellt zu sein, um EU-Asylpolitik wirkungsvoll mitzugestalten. Noch fehlt es an kohärenten Konzepten, die sowohl innovativ als auch umsetzbar sind. Hier setzt das vorliegende Papier an. Es zeigt die finanziellen und strukturellen Defizite der Kommunen in der Flüchtlings- und Asylpolitik auf und entwickelt konkrete Ideen, wie Kommunen nachhaltig gestärkt und ihr Potenzial für die Weiterentwicklung eines gemeinsamen europäischen Asylsystems genutzt werden kann. Kommunen sollen beispielsweise einen verbesserten Zugang zu EU-Fonds und Mitspracherechte bei der Aufnahme von Schutzsuchenden erhalten. Gleichzeitig nehmen die Vorschläge aber auch das Selbst-bestimmungsrecht von Schutzsuchenden ernst: Nur wenn Geflüchtete ihren Wohnort selbst mit aussuchen können, wird Sekundärmigration nennenswert reduziert. Die Vorschläge greifen Ideen aus Politik und Wissenschaft auf, verbinden vielversprechende Ansätze aus der Fachdebatte und entwickeln sie weiter. Sie wurden mit Expert/innen aus Wissenschaft und Praxis sowie Politiker/innen verschiedener politischer Lager diskutiert. Besonders prominent vertrat Gesine Schwan schon früh die Forderung, Kommunen als eigenständigen Akteur in der EU-Flüchtlingspolitik durch einen EU-Fonds finanziell zu stärken. In der Politik wurden diese und ähnliche Forderungen auch durch grüne Abgeordnete, wie z.B. Franziska Brantner, oder auch durch Frankreichs Präsident Emmanuel Macron aufgegriffen. Die Formulierung der Vorschläge richtete sich vor allem an ihrer politischen Umsetzbarkeit und Praktikabilität aus. Dementsprechend können die Empfehlungen im Einklang mit nationalstaatlicher Politik an die jeweiligen Strukturen und Verfahren im Mitgliedstaat umgesetzt werden. Sie lassen sich in drei Gruppen einteilen: die Ausgestaltung europäischer Fornds, die Stärkung von Mehrebenen-Governance sowie die Entwicklung eines kommunalen Relocation-Mechanismus. <p
Keywords: Flüchtlings- und Asylpolitik der EU; Städtenetzwerke; Krise

Der Weg über die Kommunen: Empfehlungen für eine neue Schlüsselrolle der Kommunen in der Flüchtlings- und Asylpolitik der EU - Bendel, Petra; Schammann, Hannes; Heimann, Christiane; Stürner, Janina (2019)
Die Flüchtlings- und Asylpolitik der Europäischen Union steckt in einer Sackgasse. Die Lasten der Aufnahme von Schutzsuchenden aus den Krisenregionen in Europas Umfeld sind ungerecht verteilt. So verweigern einige Staaten die Aufnahme, indes andere durch Regelungen wie das Dublin-Abkommen mit einer großen Zahl von Flüchtlingen überfordert werden. Interessant ist, dass gerade dort, wo die größte Last der Integration geschultert wird, besondere Ansätze für eine Migrations- und Integrationspolitik zu finden sind – nämlich in den Kommunen, europaweit. Das vorliegende Policy Paper „Der Weg über die Kommunen“, in Auftrag gegeben von der Heinrich-Böll-Stiftung, plädiert daher für eine aktivere Rolle der Kommunen in der Asyl- und Flüchtlingspolitik, bezieht die Erfahrungen von Modellprojekten ein und entwickelt daraus eine Reihe von Empfehlungen für die Politik.
Keywords: Kommunen; Flüchtlings- und Asylpolitik; EU

Evaluation Report of the Urban Partnership on Inclusion of Migrants and Refugees. - Stürner, Janina; Heimann, Christine (2020)
Keywords: evaluation; EU; cities; migration

Going the (Social) Distance. How Migrant and Refugee-sensitive Urban COVID-19 Responses Contribute to the Realization of the Global Compacts for Migration and Refugees - Stürner, Janina; Bekyol, Yasemin (2021)
Keywords: Covid 19; migration; refugees; cities; city network

Local Authorities as Allies in Promoting Protection Frameworks for Mobile Urban Populations - Stürner-Siovitz, Janina; Nzamba Nzamba, Lionel (A Roadmap for Advocacy, Policy Development, and Programming: Protection in Mixed Movements along the Central and Western Mediterranean Routes 2021, 2021)

Tailored to whom? – Envisaging refugees and host municipalities as central actors for sustainable resettlement - Stürner, Janina (2019)

The EU Urban Partnership on Inclusion: Institutionalizing Local–Supranational Integration Governance - Stürner-Siovitz, Janina; Heimann, Christiane (International Migration Review, 2022)
In times when immigrant integration is considered both a highly salient political topic and a practical challenge by local, national, and European decision-makers, an analysis of the governance approach developed by the European Union (EU) Urban Partnership on Inclusion of Migrants and Refugees opens up new opportunities to advance research on migration studies’ “local turn.” In this IMR Dispatch from the Field, we argue that exploring the joint local-EU agenda-setting and cooperation in the Urban Partnership on Inclusion can refine understandings of multilevel governance. We argue that what is intriguing about the Urban Partnership on Inclusion for migration scholars is the institutionalization of local–supranational cooperation within an existing intergovernmental EU structure as a way to advance multilevel governance, even when the national level remains passive. Demonstrating the ways in which the Urban Partnership on Inclusion differs from city networks focused on questions of migration and integration, we show that the Urban Partnership on Inclusion offers a common structure to EU institutions and local authorities to coordinate agendas and actions, both from the local level upward and from the EU level downward while aiming to find ways around national passivity. Paying closer attention to such forms of institutionalized local–supranational governance developing within state-led structures, we suggest, can advance migration research and shed light on emerging local–supranational governance arrangements both at the European and the international levels.
CRIS-Team Scopus Importer:2022-07-08
Keywords: city diplomacy; European Union; multilevel governance

The time is now: Moving towards a coherent approach to protect Afghans - Stürner-Siovitz, Janina; Günther, Johanna; Schweiger, Raphaela (2022)

The Two-way ‘Glocalisation’ of Human Rights or: How Cities Become International Agents in Migration Governance - Bendel, Petra; Stürner, Janina (Peace Human Rights Governance, 2019)
‘We need to be part of U.N. decision-making if international agreements are to be responsive to on-the-ground realities’ (McCarthy 2017). Following the US government decision to withdraw from negotiating a ‘Global Compact for Safe, Orderly and Regular Migration’, local authorities such as the New York City Mayor’s Office joined forces with cities worldwide to demand a voice in international migration governance. We claim that this case illustrates an emerging strategy in city diplomacy – the two-way ‘glocalisation’ of human rights. Adopting this approach, cities localise international and European human rights law through local implementation. However, in the absence of national engagement at the international level or in the face of a negotiation deadlock, as in the current European migration and asylum debate, a window of opportunity is opening up for cities to go a step further: Cities retranslate local practices into global human rights discourses thus developing international agency to achieve three goals. 1) Cities create soft law to ensure local reception and integration policies grounded in fundamental international and European rights. 2) Through networks such as ‘EUROCITIES’ or the ‘Global Mayoral Forum’ cities lend legitimacy to EU and UN strategies and advocate rights-based migration governance holding EU and UN institutions and member states accountable by their own laws and values. 3) Based on their expertise as implementers and policy innovators, cities push for a place at the international and European negotiation tables. In this article, we present initial findings of our research on the role and activities of transnational municipal networks in the development of migration governance. We outline and illustrate cities’ glocalisation strategies with examples from the international and European context. The article concludes with concrete recommendations to the international, European, national and local level on how to incorporate cities’ transnational engagement in intergovernmental processes for truly coherent and rights-based migration governanc
Keywords: human rights; migration governance; city networks; city diplomacy; glocalisation

Valuing Local Ownership - Bendel, Petra; Stürner-Siovitz, Janina (FAU University Press, 2019)
With the Global Compact on Refugees, the International Community seeks to highlight the importance of multi-stakeholder approaches in the search for sustainable solutions to displacement. However, when it comes to planning and implementing durable solutions, two of the main actors are often absent or even excluded from decision-making – these are refugees and hosting municipalities. The two papers in this publication highlight central bottlenecks for participatory approaches in both resettlement schemes as well as camp accommodation. Based on an analysis of existing good practice and new policy approaches, the first paper develops an innovative proposal for a Municipal Resettlement Programme while the second paper critically discusses potentials and risks of adapting special zones concepts to displacement contexts. Together, both papers are a call for action to actively engage refugees and communities so as to find answers to the question of “who could thrive where
Keywords: cities; empowerment; local turn; migration; municipalities; ownership; participation; refugee camp; refugees; resettlement; self-reliance; special economic zone; urban displacement

Valuing Local Ownership - Refugees and Municipalities as Actors in the Search for Sustainable Solutions to Displacement - Bendel, Petra; Stürner, Janina (FAU University Press, 2019)
With the Global Compact on Refugees, the International Community seeks to highlight the importance of multi-stakeholder approaches in the search for sustainable solutions to displacement. However, when it comes to planning and implementing durable solutions, two of the main actors are often absent or even excluded from decision-making – these are refugees and hosting municipalities. The two papers in this publication highlight central bottlenecks for participatory approaches in both resettlement schemes as well as camp accommodation. Based on an analysis of existing good practice and new policy approaches, the first paper develops an innovative proposal for a Municipal Resettlement Programme while the second paper critically discusses potentials and risks of adapting special zones concepts to displacement contexts. Together, both papers are a call for action to actively engage refugees and communities so as to find answers to the question of “who could thrive where?”
Keywords: refugees; social integration; municipality; resettlement

Wahrheit auf der Flucht? Potenzial und Engagement der syrischen Diaspora in Deutschland für Wahrheitsfindung, Dialog und Friedensförderung - Stürner, Janina (Zeitschrift für Menschenrechte, 2019)
Keywords: human rights; refugees; Syria

What Role for African Cities in Urban Migration Governance? - Stürner-Siovitz, Janina; Nzamba Nzamba, Lionel (2022)
Keywords: Refugees; Africa; cities; protection; displacement

When Mayors make Migration Policy: The Future of City Diplomacy - Heimann, Christine; Stürner, Janina; Bendel, Petra; Schammann, Hannes (2021)
Keywords: cities; EU; governance; migration; city diplomacy

'When Mayors make Migration Policy’: What role for cities in EU migration and integration policymaking? - Bendel, Petra; Heimann, Christiane; Schammann, Hannes; Stürner, Janina (2020)
EU institutions and a growing number of member states are starting to recognise municipal actors as important players in integration governance. However, moving away from ad hoc exchanges on integration towards more structural forms of cooperation, and opening up migration policy debates to local input remains challenging. Building on an analysis of the benefits of proactive cooperation between local authorities and EU institutions, this Policy Brief presents recommendations to (i) strengthen the local impact on supranational policymaking; (ii) link migration and integration policies through the inclusion of municipalities; and (iii) mitigate the urban-rural divid
Keywords: EU; migration; integration; municipal actors